Study of Chemical and Enzymatic Hydrolysis of Cellulosic Material to Obtain Fermentable Sugars - Myriam A. Amezcua-Allieri; Teresa Sánchez Durán; Jorge Aburto (Journal of Chemistry)
The objective of this study was to evaluate the chemical and enzymatic hydrolysis using a factorial experimental design (23) in order to obtain fermentable sugars from cellulose-based material (CBM) usually used as pet litter. In assessing chemical hydrolysis, we studied the effect of temperature, in addition to H2SO4 concentration and reaction time, on the production of total sugars, reducing sugars, soluble lignin, carbohydrate profile, furfural (F), and hydroxymethyl furfural (HMF). We performed a response surface analysis and found that, at 100°C, 1% acid concentration, and 60 min reaction time, the yields of 0.0033 g reducing sugar/g biomass and 0.0852 g total sugars/g biomass were obtained. Under the above conditions, F is not generated, while HMF is generated in such a concentration that does not inhibit fermentation. We pretreated the CBM with H2SO4, NaOH, CaO, or ozonolysis, in order to evaluate the effectiveness of the enzymatic hydrolysis from the pretreated biomass, using an enzymatic cocktail. Results showed that CBM with acid was susceptible to enzymatic attack, obtaining a concentration of 0.1570 g reducing sugars/g biomass and 0.3798 g total sugars/g biomass. We concluded that acid pretreatment was the best to obtain fermentable sugars from CBM.